Studies of Pseudomonas aeruginosa Mutants Indicate Pyoverdine as the Central Factor in Inhibition of Aspergillus fumigatus Biofilm. (4th October 2017) - Sass, Gabriele; Nazik, Hasan; Penner, John; Shah, Hemi; Clemons, Karl V; Groleau, Marie-Christine; Déziel, Eric; Stevens, David A
Abstract: Background: Pseudomonas aeruginosa (Pa) and Aspergillus fumigatus (Af) are common opportunistic bacterial and fungal pathogens, respectively. They often co-exist in airways of immunocompromised patients and individuals with cystic fibrosis, where they form biofilms and cause acute and chronic illnesses. Hence, the interactions between them have long been of interest, and known that Pa can inhibit Af in vitro. Methods: We have approached the definition of the inhibitory Pa molecules by studying 24 Pa mutants, with various genes deleted, for their ability to inhibit Af biofilms. The ability of Pa cells, or their extracellular products produced during planktonic or biofilm growth, to affect Af biofilm formation, preformed Af biofilm, or planktonic Af was studied in agar and liquid assays with conidia or hyphae. Results: Four mutants, pvdD -/pchE-, pvdD-, lasR-/rhlR-, and lasR were shown defective in the various assays. This suggested a central place for the siderophore pyoverdine as the key inhibitory molecule, although additional quorum sensing-regulated factors likely contribute to the deficiency of the latter two mutants. Studies of pure pyoverdine substantiated these results and restored inhibition by pyoverdine deletion mutants. Added iron or hemin reversed the inhibition by pyoverdine or pyoverdine-producing Pa strains. Conclusion: The key inhibitor for Af biofilms produced by Pa is pyoverdine. The inhibitory mechanism is chelation of iron, and denial of iron to Af. Disclosures: All authors: No reported disclosures.